Efforts to Optimize Injector Performance for The Combustion Process in The Diesel Generator on The Mt. Gas Patra 3 - Ardhika K, Wildan; Alamsyah, Jaya; Effendi, Effendi; Mangatur Tampubolon, Brenhard (Greenation Research & Yayasan Global Resarch National, 2023)
The injector is a component that functions to atomize fuel in the combustion process, the performance of this injector is very influential on whether or not the combustion process is complete in a diesel generator. The combustion process is very important so that the diesel generator gets optimal performance so that it can properly supply the electricity needs on board. The research method used is descriptive qualitative using data analysis techniques using fishbone diagrams and using data collection techniques through interviews, observation and documentation studies. The indications that appear about the not optimal fogging is the high temperature of the exhaust gas, the exhaust gas is black in color and detonation appears. After analysis, several causes were found, one of which was a lack of pressure on the injector.